2010
DOI: 10.1111/j.1743-6109.2009.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Women’s Sexual Interest Diagnostic Interview—Short Form (WSID-SF) and a Daily Log of Sexual Activities (DLSA) in Postmenopausal Women with Hypoactive Sexual Desire Disorder

Abstract: Introduction Currently, there is no clear standard assessment tool for the diagnosis and daily monitoring of hypoactive sexual desire disorder (HSDD) in postmenopausal women. Aim The aim of the study was to validate (i) the Women’s Sexual Interest Diagnostic Interview—Short Form (WSID-SF) which is a structured tool to identify HSDD; and (ii) the Daily Log of Sexual Activities (DLSA) which is a diary to monitor daily HSDD stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A number of well-validated self-and clinician-administered questionnaires are available, including the Female Sexual Function Index (FSFI), a 19-item self-report measure of FSD that scores on 6 domains of sexual function (desire, arousal, lubrication, orgasm, satisfaction, and pain), as well as a total score, 32 and has been validated in women with HSDD; 33 the PFSF, a 37-item instrument, measures the loss of sexual desire and related aspects of sexual function in menopausal women with HSDD; 28,34 the Sexual Interest and Desire Inventory-Female Version (SIDI-F), a clinicianadministered tool to quantify the severity of symptoms in women with HSDD, 35,36 and the validated Women's Sexual Interest Diagnostic Interview (WSID), an assessment tool designed to help clinicians identify HSDD in postmenopausal women. [36][37][38] Shorter questionnaires have also been developed and validated for use in busy clinical practice, including the brief version of the PFSF, developed using items from the PFSF and the PDS and validated in HSDD, 39 a 4-item HSDD screener, which can be paired with a face-to-face interview by the primary care clinician to reliably screen for HSDD in postmenopausal women, 26 and the Decreased Sexual Desire Screener (DSDS), a 5-item questionnaire developed for practicing clinicians who are neither trained nor specialized in managing FSD. These brief diagnostic screening tools are designed to assist clinicians in making an accurate diagnosis of generalized acquired HSDD.…”
Section: Psychometric Instrumentsmentioning
confidence: 98%
“…A number of well-validated self-and clinician-administered questionnaires are available, including the Female Sexual Function Index (FSFI), a 19-item self-report measure of FSD that scores on 6 domains of sexual function (desire, arousal, lubrication, orgasm, satisfaction, and pain), as well as a total score, 32 and has been validated in women with HSDD; 33 the PFSF, a 37-item instrument, measures the loss of sexual desire and related aspects of sexual function in menopausal women with HSDD; 28,34 the Sexual Interest and Desire Inventory-Female Version (SIDI-F), a clinicianadministered tool to quantify the severity of symptoms in women with HSDD, 35,36 and the validated Women's Sexual Interest Diagnostic Interview (WSID), an assessment tool designed to help clinicians identify HSDD in postmenopausal women. [36][37][38] Shorter questionnaires have also been developed and validated for use in busy clinical practice, including the brief version of the PFSF, developed using items from the PFSF and the PDS and validated in HSDD, 39 a 4-item HSDD screener, which can be paired with a face-to-face interview by the primary care clinician to reliably screen for HSDD in postmenopausal women, 26 and the Decreased Sexual Desire Screener (DSDS), a 5-item questionnaire developed for practicing clinicians who are neither trained nor specialized in managing FSD. These brief diagnostic screening tools are designed to assist clinicians in making an accurate diagnosis of generalized acquired HSDD.…”
Section: Psychometric Instrumentsmentioning
confidence: 98%
“…A subgroup of 175 subjects were also interviewed by an experienced clinician. The current study demonstrated good diagnostic sensitivity (70%) and specificity (89%) with a kappa coefficient of 0.46 reflecting agreement on the diagnosis of HSDD between the clinician and the WSID‐SF [70].…”
Section: Resultsmentioning
confidence: 61%
“…Interestingly, the interrater reliability was assessed and found adequate using trained actresses in video-taped situations. Based on the preliminary investigations, the short from was developed (WSID-SF) in a study on 629 postmenopausal women aged 39-66 years evaluated for HSDD [70]. The WSID-SF is a nine-item questionnaire and includes questions about distress.…”
Section: Women's Sexual Interest Diagnostic Interview (Wsid) and The mentioning
confidence: 99%
“…The IVR versions of these measures have been favored by the FDA for use in registration trials in psychiatry and sleep medicine. More recently, IVR versions of other well-known measures have been developed and validated for use in female sexual dysfunction [8], type 2 diabetes [9], HIV-AIDS [1012], chronic lung disease [13], prostate cancer [14], and various other diseases and indications. Among the advantages by study sponsors and regulatory agencies, use of IVR for data collection has been shown to provide accuracy and reliability of recording, reduce recall errors and improve reliability versus paper measures, and provide firm documentation of time and date of data entry [16].…”
Section: Introductionmentioning
confidence: 99%